Human Trafficking and the Rome Statute of the International Criminal Court - Moran, Clare Frances (The Age of Human Rights Journal, 2014)
The case for extending the reach of the Rome Statute to the crime of human trafficking has not yet been made in detail. The brutality which occurs when human beings are trafficked by criminal gangs is of an equally egregious nature as the other crimes covered by the Rome Statute and yet it does not fall within the remit of the International Criminal Court. Such trafficking may also fall outwith the definition of slavery as a crime against humanity, particularly given the State policy threshold set by the Statute. This paper seeks to explore the viability of the inclusion of human trafficking as a discrete international crime within the Rome Statute as a response to this loophole.